BRIDGING OPENNESS AND ARCHIVING: A CASE STUDY OF PUBLIC INFORMATION DISCLOSURE POLICY THROUGH PPID ANRI - Catur Rahmawati Tejaningrum; Achmad Danu; Asropi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The disclosure of public information is a key principle for achieving transparent, participatory, and accountable governance. As a national archival institution, the National Archives of the Republic of Indonesia (ANRI) plays a crucial role in facilitating public information disclosure, particularly through its Information and Documentation Management Officer (PPID). This study analyzes the implementation of the public information disclosure policy by the ANRI PPID, along with the challenges and strategies encountered in reconciling the need for openness with the protection of archives. This qualitative case study employed policy analysis, in-depth interviews, and reviews of internal documentation. Findings indicate that while the ANRI PPID has introduced several innovations, it still faces challenges related to the integration of information systems, categorizations of information types, and public awareness of the right to access information. This study suggests enhancing the institutional capacity of the PPID, improving public information literacy, and aligning information disclosure policies with archival principles. This study aims to contribute to advancing public information governance that effectively balances transparency with safeguarding information.